Juvenile myoclonic epilepsy: neurophysiological aspects - O. S. Shilkina (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2018)
The review presents an update on the electroencephalographic characteristics and neurophysiology of juvenile myoclonic epilepsy (JME) in Russia and foreign countries.Materials and methods. The authors have performed a literary search for the full-text publications on JME electroencephalography and neurophysiology worldwide and in the Russian Federation, which are available in Russian and foreign databases.Results and discussion. Analysis of the literature suggests that JME patients have some electroencephalographic pattern features that include the atypical morphology of spike-and-slow-wave  complexes, as well as amplitude asymmetry, focal discharges, focal  onset of paroxysms, focal paroxysmal shift, and generalized paroxysmal fast rhythm.The analysis of the literature also indicates that primary care neurologists, clinical neurophysiologists, and epileptologists should be informed about the electroencephalographic characteristics of JME to timely diagnose the disease and to rule out the use of inadequate therapy.